991. Psychosocial Factors and HIV Risk among Transgender Women Living in Miami. (31st December 2020) - Rodriguez, Jornan; Salguero, Douglas; Abbamonte, John M; Botero, Patricia Raccamarich; Valeria; Montgomerie, Emily K; Savita, Pahwa; Martinez, Claudia; Rodriguez, Allan; Alcaide, Maria L; Raccamarich, Patricia; Solorzano, Dalhila
Abstract: Background: Transgender (TG) women are disproportionately affected by HIV infection and have poor health outcomes when compared to cisgender women. This study evaluates psychosocial factors, and HIV risk among transgender women with and without HIV infection living in Miami, the city with the highest incidence of HIV in the US. Methods: Adults who identified themselves as TG living in Miami were recruited from the community and local clinics. Self-reported HIV status, sociodemographic, behavioral data (HIV risk behaviors, sexual partners, illicit substance and alcohol use), and psychosocial factors (depression, violence or abuse events, and HIV stigma) were collected with questionnaires into RedCap. Results: A total of 22 participants completed assessments. Ten (45.5%) indicated being HIV uninfected (HIV-) and 12 (54.5%) had been diagnosed with HIV (HIV+). A total of 15 (68%) participants reported use of feminizing hormones and 11 (50%) had undergone feminizing surgeries. Median age was 55 (20, 69); 15 (69%) were white and 5 (23%) Black; 15 (69%) were of Hispanic ethnicity; Level of education 11 (12; 1.8) 12(55%) had completed at least high school; 2 (9%) were employed. 16 (73%) reported being sexually active in the previous month; median number of partners in the last month was 1.5 (1; 2.13); only 13 (60%) reported consistent condom use in the last sexual encounter; 14 (64%) engaged in receptive anal sex; 9 (41%) reported ever engaging in sex for money. Violence or abuse events were common, and participants had experienced an average of 3.9 lifetime events (Median = 3; SD = 3.45). Depression measured by the BSI-18 scale revealed low depression scores (Mean = 1.77; SD = 0.82). HIV infected participants were more likely to be black (p=0.05) and unemployed. We did not find significant differences by HIV status in other variables, including depression and violence or abuse. Among HIV+ participants, HIV stigma measured by the 'Stigma Scale' was low (Mean = 1.71; SD = 0.41). Conclusion: We identified high rates of events of violence or abuse, that did not differ by HIV status. HIV infection was more common among black TG women.Further research is necessary to identify potential targets for HIV prevention and care in the vulnerable population of TG women. Study funded by the Miami CFAR (P30AI073961) Disclosures: All Authors : No reported disclosures